Evaluation of the teaching recovery techniques community-based intervention for accompanied refugee children experiencing post-traumatic stress symptoms (Accompanied refugeeS In Sweden Trial; ASsIST): study protocol for a cluster randomised controlled trial. Issue 7 (26th July 2020) - Warner, Georgina; Durbeej, Natalie; Salari, Raziye; Fängström, Karin; Lampa, Elin; Baghdasaryan, Zaruhi; Osman, Fatumo; Gupta Löfving, Sandra; Perez Aronsson, Anna; Feldman, Inna; Sampaio, Filipa; Ssegonja, Richard; et al.
Abstract : Background: Refugee children have often experienced traumas and are at significant risk of developing mental health problems, such as symptoms of post-traumatic stress disorder (PTSD), depression and anxiety, which can continue for years after resettlement. The Accompanied refugeeS In Sweden Trial (ASsIST) aims to evaluate a community-based intervention, called 'Teaching Recovery Techniques' (TRT), for accompanied refugee minors experiencing PTSD symptoms. Methods/design: A cluster randomised controlled trial will be conducted in which participants will be randomly allocated to one of the two possible arms: the intervention arm (n=113) will be offered the TRT programme and the waitlist-control arm (n=113) will receive services as usual, followed by the TRT programme around 20 weeks later. Outcome data will be collected at three points: pre-intervention (T1), post-intervention (T2; c.8 weeks after randomisation) and follow-up (T3; c.20 weeks after randomisation). Ethics and dissemination: Ethical approval was granted by the Regional Ethical Review Board in Uppsala (Ref. 2018/382) (24 th February 2019). Results will be published in scientific journals. Trial registration details: ISRCTN17754931 . Prospectively registered on 4 th June 2019.